Perancangan Sistem Informasi Manajemen Ijazah dan Transkrip Nilai Baru di Institut Teknologi Garut - Nuraeni, Fitri; Kurniadi, Dede; Hadi Wijaya, Tryana (Institut Teknologi Garut, 2023)
Submission of diplomas and grade transcripts is an important process in the management of education in tertiary institutions. However, at the Garut Institute of Technology (ITG), the process of submitting diplomas and grade transcripts is still conventional, resulting in obstacles such as long queues and difficulty accessing students who are outside the campus. To overcome these problems, this study aims to design and develop an efficient and integrated management information system for filing new diplomas and grade transcripts. The method used in this study is the Extreme Programming (XP) method. Software development is carried out by utilizing web technology and features such as validation, submission monitoring, email notifications, and submission logs. Students can apply for diplomas and transcripts online through the platform provided, fill out the online submission form, and upload the required documents. Related units, such as BAAK, Libraries, BAK, CDC, LP3B, and Study Programs, can carry out validation and verification processes online. Students can also monitor the progress of their submissions through the monitoring feature and receive notifications via email.